Soil organic matter fractions in humid tropics as influenced by application of crop residues - Mubarak, A. R.; A. B., Rosenani (2003)
The contribution of crop residues to soil organic matter (SOM) in the sand size (particulate organic matter, POM) and sodium (Na) Iodide light (NAL) fractions were determined from soil samples (0-20 cm) collected from an experiment (April 1997-August 1999) studying the contribution of crop residues in sustaining yields of maize (Zea mays L.) and groundnut (Arachis hypogaea L.) in a crop rotation system. The treatments were: recommended inorganic fertilizer (NPK) with crop residues (T1), recommended inorganic fertilizer without crop residues (T2), and half dose of the recommended inorganic fertilizer with crop residues and combined with 10 t ha-1 chicken manure (T3). Soil organic matter size fractionation was carried out for samples collected after harvest of the second (1998) and fourth (1999) crop whereas density fractionation was carried out for samples collected after harvest of the fourth crop. Results showed that dry matter content of the POM, organic carbon (C) and nitrogen (N) relative to total soil dry weight, total soil C and total soil N in T1 and t3 plots were statistically similar to T2 plots. For all treatments, these values were found to be 1.8-3.3%, 8.5-18.1% and 4.1-7.8% for total dry matter, content of C and N, respectively. After two years, 67% of the POM dry matter weight was recovered in the small size (0.125-0.053 mm) compared to 13% in the 2.0-0.25 mm size particles. Also for all treatments, C and N in the light fractions (LF) were 0.5-0.7%, 0.6-2.1%, 0.4-1.0% (in the free LF) and 0.03-0.08%, 0.02-0.09%, 0.04-0.09% (in the occluded LF). Dry matter content of the occluded organic matter was significantly (P ≤ 0.05) lower in T3 plots (0.93%) compared to T1 and T2 (0.13-0.2%). It was concluded that during application of organic inputs in the humid tropics, two years study was not sufficient for positive accumulation of labile SOM.